The Education Assessment Capacity Structure of Primary Teachers in Vietnam - Khanh, Nguyen Cong; Huong, Do Thi (VNU Journal of Science: Education Research, 2018)
Education assessment capacity is considered to be indispensable for teachers at all levels. However, there are currently many difficulties in assessing this capacity, especially for primary teachers when there is a change in assessing students. In this report, we would like to suggest a education capacity assessment structure for primary teachers and to demonstrate such structure through a survey of primary teachers' assessment capacity in Vietnam. Survey results show that the education assessment capacity structure consists of 6 component competencies which suitable for primary teachers in Vietnam. And, the report also points out that Vietnamese primary teachers' education assessment capacity in Vietnam is currently evaluated at a fairly good level.